Helical and Spiral Antennas as Electric Small Antennas - Papageorgiou, Christos D. (European Journal of Applied Sciences, 2023)
The simplest form of a classical antenna is the dipole antenna, which is essentially two pieces of wire placed end to end with a feed point in the middle. The length of this antenna is typically half the wavelength of the signal that is being received or transmitted. An “electric small” antenna is defined as an antenna of much shorter dimensions than the wavelength of the signals it is designed for. Small electric antennas have an advantage when space is the most essential factor. Satellites and mobile communication apparatuses for example can use small antennas in order to free up more space for other components. The problem with classical electric small antennas is that their bandwidth and radiation efficiency shrink as they get shorter. Although such antennas have been in use for decades, they remain difficult to design and limited in their applicability. However, the classic approach of studying metal antennas using only Maxwell equations limits the real internal nature of them as metal lattice structures and thus as quantum wells of free electrons. When interpreted this way, free electrons are obeying the Schrodinger wave equation and this view can give new ideas for designing effective curvilinear electric small antennas. Such a class of electric small helical and spiral antennas is proposed in the following paper.